Salivary Biomarkers CYFRA 21-1 and MMP9: Predictive Indicators of Disease Progression in Oral Squamous Cell Carcinoma - Waqar-un-Nisa, Moomal Aslam Khan, Faiza Agha, Shumaila Khan, Sara Fatima, Padma Rathore, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Oral squamous cell carcinoma (OSCC) is a prevalent cancer with high mortality rates. Identifying non-invasive biomarkers for early diagnosis and monitoring the disease's progression is crucial. Objective: This study aims to assess the salivary levels of CYFRA 21-1 and MMP-9 in OSCC patients and their correlation with clinicopathological characteristics and histological grades. Methods: A total of 90 participants, including 45 healthy controls and 45 OSCC patients, were enrolled. Demographic and clinicopathological data were collected, including gender, habits (smoking, gutkha, betel nut, pan/naswar), habit duration, and tumor site. Salivary levels of CYFRA 21-1 and MMP-9 were measured using enzyme-linked immunosorbent assay (ELISA). The OSCC patients were categorized into well-differentiated, moderately differentiated, and poorly differentiated histological grades. Results: Among OSCC patients, males (78%) were predominant. Smoking and gutkha use were the most common habits. The highest percentage of patients reported habit durations >16 years. CYFRA 21-1 and MMP-9 levels were significantly higher in poorly differentiated OSCC compared to moderately and well-differentiated cases (p = 0.01 and p = 0.002, respectively). MMP-9 levels showed a significant increase with longer habit durations (p = 0.002). The tumor site predominantly involved the tongue, especially in poorly differentiated cases (46.6%). Conclusion: Salivary CYFRA 21-1 and MMP-9 are promising biomarkers for OSCC, with elevated levels correlating with histological grade and habit duration. These biomarkers may aid in early diagnosis and monitoring the progression of OSCC. Keywords: CYFRA 21-1, MMP-9, Oral Squamous Cell Carcinoma, Saliva, Histological Grade.